2016
DOI: 10.1002/jcb.25474
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cFLIPL Determines the Basal Interaction of Bcl‐2 With Beclin‐1 and Regulates p53 Dependent Ubiquitination of Beclin‐1 During Autophagic Stress

Abstract: Autophagy and apoptosis are two different physiological processes, which is required for the maintenance of cellular homeostasis. The apoptosis associated proteins such as Bcl-2 and p53 have a close association with autophagic proteins HMGB1 and Beclin-1 to modulate autophagic signaling. We demonstrate here the involvement of anti-apoptotic protein cFLIPL in the regulation of autophagy during cellular stress. We found that ectopic expression of cFLIPL decreases the sensitivity of HEK 293T cells against rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…MiRNAs act through downregulating multiple target genes, while Beclin-1 is known as a key initiator of the autophagic process 27. The authors reported that miR-384 could modulate autophagy to anti-atherosclerosis by inhibiting Beclin-1 expression 28.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs act through downregulating multiple target genes, while Beclin-1 is known as a key initiator of the autophagic process 27. The authors reported that miR-384 could modulate autophagy to anti-atherosclerosis by inhibiting Beclin-1 expression 28.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of FADD, stimulation of TNF-α significantly enhances ROS level and ubiquitination of cFLIP L in HEK 293T cells. Moreover, knockdown of the cFLIP L has been reported to augment ROS generation and JNK activation in tumor cells 28 62 . We demonstrate here that knockdown of cFLIP L in TNF-α primed cells progressively enhance the ROS accumulation and JNK1 activation, but this effect was counterbalanced in NAC pre-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic HMGB1 is able to bind directly to beclin1, an important autophagy initiator, allowing it to form autophagy initiation complexes, which can remove harmful oxidative stresses (e.g., from mitochondria) . HMGB1 is able to bind beclin1 by displacing Bcl2, an apoptosis inhibitor, which once dissociated from beclin1 can perform its role in preventing programmed apoptotic cell death . Binding of HMGB1 to beclin1 occurs in the area of C23 and C45 and mutation of these cysteines to prevent disulfide bridge formation also prevents beclin1 association and diminishes autophagy (Fig.…”
Section: Redox Regulation Of Hmgb1 Functionmentioning
confidence: 99%